Antibiotic susceptibility of P. mirabilis isolated from clinical samples in Thi- Qar province - Owaied, Huda; Jabur, Sanaa (University of Thi-Qar Journal of Science, 2022)
Proteus spp. Is a motile dimorphic Gram negative bacteria belonging to the order Enterobacterales. P. mirabilis, the most commonly isolated species from clinical samples. The present study aimed to investigate the resistance of Proteus mirabilis isolates to different antibiotics. The study included the collection of 487 samples from different clinical sources, including urine, burns, wounds, ear swabs and diabetic ulcers. Different ages were involved of both sexes. Samples were collected from patients attending Al-Nasiriya and Al- Hussain Teaching Hospitals and private laboratories in Thi-Qar province, Iraq, from 29th of November 2021 to 20th of Abril 2022. A total of the isolates were diagnosed by different laboratory tests. The prevalence of P. mirabilis was 8.6 % among all collected samples. Female infection rate was 52.4%, male infection rate was 47.6 %. The age group ≥ 44 years was most commonly infected with P. mirabilis. In addition most P. mirabilis isolates were obtained from UTIs 45%. The antibiotic susceptibility test results showed a high resistance for Cefepime 83.3%, Ceftriaxone 78.8%, Tobramycin 73.3%, Ampicillin 71.4%, Amoxicillin/clavulanic Acid 69%, and Cefotaxime 60%. However, ciprofloxacin was the highest effective antibiotic 54.7%, followed by Meropenem 50%, and Gentamicin 45%. Finally, amikacin had intermediate activity 19%, followed by Netilmicin 16.6%.